Electrophysiological correlates of distance and direction processing during cognitive map retrieval: A source analysis - Teixeira De Almeida, Mélanie; Seeber, Martin; Gschwend, Katherina; Maurer, Roland; Faulmann, Igor; Burra, Nicolas (Frontiers in Human Neuroscience, 2023)
The cognitive map is an internal representation of the environment and allows us to navigate through familiar environments. It preserves the distances and directions between landmarks which help us orient ourselves in our surroundings. In order to investigate the neural correlates of the cognitive map, we used the Cognitive Map Recall Test, in which participants had to estimate distances and directions between familiar landmarks tailored to their own knowledge. Theta waves have been shown to be implicated in spatial navigation and we examined their role in the cognitive map, as well as the brain regions that generated them. To that aim, we performed electroencephalographic source imaging while focusing on frequency spectral analysis. We observed increases of theta amplitude in the frontal, temporal, parahippocampal gyri and temporal poles during the recall of the cognitive map. We also found increases of theta amplitude in the temporal pole and retrosplenial cortex during manipulation of directions. Overall direction processing induces higher theta amplitude than distance processing, especially in the temporal lobe, and higher theta amplitude during recall compared to manipulation, except in the retrosplenial cortex where this pattern was reversed.